'Out of the frying pan': the challenges of prescribing for insomnia in psychiatric patients. (June 2014) - Huthwaite, Mark; Cleghorn, Mark; MacDonald, Joanna
Objectives: Managing insomnia is a common challenge for psychiatrists and their patients. We have observed an increasing use of quetiapine as a hypnosedative. Methods: We conducted an audit with the aim of establishing the prescribing patterns of local general psychiatrists in New Zealand, comparing them with established guidelines and determining the extent of the prescribing of quetiapine as a hypnosedative. Participant psychiatrists were recruited from peer review groups. Each participant provided anonymised prescribing information from 10 patients and noted their intention when prescribing. Results: Twenty-five clinicians (58% response rate) responded with prescriptions for 100 in-patients and 177 community mental health patients. 60% of in-patients and 62% of community patients were prescribed medications to aid with sleep. The most commonly prescribed medications were zopiclone, quetiapine and benzodiazepines. Prescribing adhered with the recommended guidelines for 20% of benzodiazepine and 35% of zopiclone prescriptions. Two thirds (60%) of the community prescriptions for quetiapine were primarily for hypnosedation. Conclusions: There is little concordance between guidelines for hypnosedative prescribing and the practices of general psychiatrists. Less zopiclone and fewer benzodiazepines were prescribed than in other studies, while more quetiapine was prescribed. The 'off-label' use of quetiapine and the duration of zopiclone and benzodiazepine use are discussed.